2015
DOI: 10.1037/h0101057
|View full text |Cite
|
Sign up to set email alerts
|

Comparing individual delay discounting of gains and losses.

Abstract: Choices between immediate and delayed consequences have been studied using mathematical models. Several studies have investigated this delay discounting phenomenon using appetitive stimuli, but few have studied it with aversive stimuli, although the models that describe the appetitive scenario have been suggested to also describe the aversive scenario. The aim of this study was to compare the delay discounting of gains and losses. Participants included 36 volunteers (undergraduate students; age range: 18–28 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 44 publications
3
21
0
3
Order By: Relevance
“…Several studies have supported the sign effect (Abdellaoui et al, ; Estle et al, ; Gonçalves & Silva, ; Mitchell & Wilson, ). As illustrated by the curves and AUC measures, in the current study the discounting curves for hypothetical monetary gains were considerably steeper than for losses on both an individual and an aggregate level, confirming the sign effect.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several studies have supported the sign effect (Abdellaoui et al, ; Estle et al, ; Gonçalves & Silva, ; Mitchell & Wilson, ). As illustrated by the curves and AUC measures, in the current study the discounting curves for hypothetical monetary gains were considerably steeper than for losses on both an individual and an aggregate level, confirming the sign effect.…”
Section: Discussionmentioning
confidence: 91%
“…The sign effect (Frederick et al, ), steeper discounting with gains than losses, is visualized by the discounting curve for gains being significantly steeper than the discounting curve for losses. The sign effect is a robust finding when dealing with hypothetical money (e.g., Estle et al, ; Frederick et al, ; Gonçalves & Silva, ; Thaler, ), but results from studies conducted on preferences for deferred real losses are ambiguous. Some early studies have supported the conclusion that subjects prefer aversive outcomes, such as small monetary losses, to be delayed (Yates & Watts, ).…”
Section: The Sign Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This was statistically confirmed by the factor condition (ascending vs. descending delays) having a nonsignificant effect on all of the variables that were analyzed. Research on the comparison between the temporal discounting of positive and negative consequences has found interesting differences between the two processes; for example, it has been found that positive reinforcers are discounted more steeply than aversive consequences (Estle et al, 2006;Gonçalves & Silva, 2015). However, the generality of these conclusions is limited because only humans have participated in this research and because the consequences employed have been mainly hypothetical.…”
Section: Discussionmentioning
confidence: 96%
“…In their laboratory study of the discounting of delayed monetary losses, Gonçalves and Silva () used a three‐group classification scheme similar to that used by Myerson et al (). About 40% of the participants in the Gonçalves and Silva study showed a typical delay discounting pattern (loss becoming less aversive with delay), but another 40% showed initial discounting followed by a decrease in degree of discounting at increasingly longer delays (loss becoming more aversive with delay), and about 20% showed no discounting.…”
mentioning
confidence: 99%